Seasonal Effect on Milk Composition, Somatic Cell Content and Milk Coagulation Properties of Italian Holstein-Friesian Cows - Simone, Beux; Martino, Cassandro; Aparecido de, Lima Vanderlei; Nogueira Alessandro, Zielinski Acácio Antonio Ferreira; Nina, Waszczynskyj (Emirates Journal of Food and Agriculture, 2019)
This study investigated the seasonal effect on composition, somatic cell content and coagulation properties of bovine milk during two different periods of the year (summer and autumn). 592 samples of raw milk from Italian Holstein-Friesian cows from different locations in the Veneto region, Italy, were collected. The samples were submitted to the following analyses: fat, protein, casein and lactose percentages and pH by infrared spectroscopy; somatic cell counting by optical fluorescence and milk coagulation properties expressed in rennet coagulation time (RCT, min) and curd firmness or consistency 30 minutes after the addition of rennet (a30, mm) by lactodinamography. The index of the aptitude of milk to coagulate (IAC) was also determined from the lactodinamographic parameters that were obtained. To verify the environmental conditions, the temperature humidity index (THI) was calculated for each collection period. No significant difference (p <0.05) was observed between protein, casein, lactose and pH in the samples collected in the summer and the autumn. However, the results for somatic cells, RCT, a30 and IAC were significantly different, with lower results in the summer. Over all the total samples analysed, 41.2% showed a milk that did not coagulate in the 30 minutes, with a higher percentage for samples collected in the summer and during this period presented lower results to of RCT, a30 and IAC; the THI values, as expected, were higher in the summer than in the autumn. The THI presented statistically different means (p <0.05), which were 73.24 in the summer and 57.43 in the autumn. Milk with this characteristic is not suitable for cheese production; however, it is suitable to produce fluid milk, or for other derivatives where enzymatic coagulation is not part of the process.